Geological history of the Pieniny Klippen Belt and Middle Jurassic black shales as one of the oldest deposits of this region – stratigraphical position and palaeoenvironmental significance - Krobicki, Michał; Golonka, Jan (Geotourism/Geoturystyka, 2018)
The main aim of this paper is presentation both general history of the Pieniny Klippen Belt and two famous sites in this region: Dunajec River Gorge and Homole Gorge. According to such general introduction the authors explain also palaeogeographical position of the Pieniny Klippen Belt Basin within Mesozoic Tethyan Ocean, and especially stratigraphical position and palaeoenvironmental conditions of Middle Jurassic black shales and their significance in geodynamic reconstruction of this basin. Both the Dunajec River Gorge, one of the most popular geotouristic object within Pieniny Mts, and Homole Gorge, one of the best place to geological study of the Pieniny Klippen Belt, are most attractive natural phenomena of this geological region. // Głównym celem niniejszej pracy jest prezentacja zarówno generalnej historii pienińskiego pasa skałkowego jak i dwóch słynnych miejsc tego regionu: przełomu Dunajca i wąwozu Homole. W nawiązaniu do takiego generalnego wprowadzenia autorzy przedstawiają również paleogeograficzną pozycję basenu pienińskiego pasa skałkowego w obrębie mezozoicznego oceanu Tetydy, a szczególnie stratygraficzną pozycję i paleośrodowiskowe warunki powstawania środkowojurajskich czarnych łupków oraz ich znaczenie w geodynamicznych rekonstrukcjach tego basenu. Zarówno spływ Dunajcem, jeden z najbardziej popularnych obiektów geoturystycznych w Pieninach, jak i wąwóz Homole, jedno z najlepszych miejsc do studiowania geologii pienińskiej, są najbardziej atrakcyjnymi obiektami przyrodniczymi w tym regionie geologicznym.